2021
DOI: 10.1186/s13256-021-03084-x
|View full text |Cite
|
Sign up to set email alerts
|

A relapsed Pseudomonas stutzeri prosthetic valve endocarditis: a case report and review of the literature

Abstract: Background Pseudomonas stutzeri is a nonfluorescent denitrifying bacterium widely distributed in the environment, and it has also been isolated as an opportunistic pathogen from humans. It is a Gram-negative bacterium and a common inhabitant of soil and water. Case presentation We report the case of a 51-year-old arab gentleman who has systemic lupus erythematous complicated by lupus nephritis and underwent renal transplantation twice. He underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…We found long-term contamination of surfaces, both from common pathogens like P. aeruginosa and less common, but increasingly appreciated pathogens like P. stutzeri ( 50 , 51 ). Hospital sinks acting as a reservoir of P. aeruginosa has been reported before ( 13 , 16 , 46 , 52 , 53 ), but here we show that persistence of these strains is common outside of an outbreak setting, and provide strong genomic evidence showing reappearance of a recently transferred isolate rather than a derivative lineage ( 18 ).…”
Section: Discussionmentioning
confidence: 94%
“…We found long-term contamination of surfaces, both from common pathogens like P. aeruginosa and less common, but increasingly appreciated pathogens like P. stutzeri ( 50 , 51 ). Hospital sinks acting as a reservoir of P. aeruginosa has been reported before ( 13 , 16 , 46 , 52 , 53 ), but here we show that persistence of these strains is common outside of an outbreak setting, and provide strong genomic evidence showing reappearance of a recently transferred isolate rather than a derivative lineage ( 18 ).…”
Section: Discussionmentioning
confidence: 94%
“…2,3 Prosthetic valve endocarditis (PVE) accounts for about 10% of all IE cases with Pseudomonas IE becoming increasingly common. 2 Halabi et al 4 and Alabdelly et al 5 both reported a rare fulminant case of P. stutzeri PVE resulting in early mortality. Casalta et al 6 reported a case of PVE caused by P. luteola after cardiac surgery leading to replacement of the aortic bioprosthetic valve.…”
Section: Discussionmentioning
confidence: 99%
“…While Pseudomonas species are rarely implicated as a cause, P. aeruginosa is the most common isolated pathogen. 2,411…”
Section: Discussionmentioning
confidence: 99%
“…S. stutzeri has been reported as a causative agent of some infections (pneumonia, meningitis, ocular infection, bacteraemia, osteomyelitis, joint infections, endocarditis), mainly in immunocompromised patients (Alwazzeh et al., 2020 ; Alabdely et al., 2021 ).…”
Section: Assessmentmentioning
confidence: 99%